2013
DOI: 10.1002/chem.201203764
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Trp‐Cage Folding Intermediate Formation

Abstract: The 20 residue long Trp-cage is the smallest protein known, and thus has been the subject of several in vitro and in silico folding studies. Here, we report the multistate folding scenario of the miniprotein in atomic detail. We detected and characterized different intermediate states by temperature dependent NMR measurements of the (15)N and (13)C/(15)N labeled protein, both at neutral and acidic pH values. We developed a deconvolution technique to characterize the invisible--fully folded, unfolded and interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 79 publications
9
65
0
Order By: Relevance
“…This structural element has been a subject of discussion in MD simulations, 2,28,32 and experimental evidence for residual flexibility at this site has been reported based on both NMR structure ensembles 8,14,19,33 and crystal structures. 23 Gai and co-workers 7 have observed a more rapid phase (ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structural element has been a subject of discussion in MD simulations, 2,28,32 and experimental evidence for residual flexibility at this site has been reported based on both NMR structure ensembles 8,14,19,33 and crystal structures. 23 Gai and co-workers 7 have observed a more rapid phase (ca.…”
Section: Discussionmentioning
confidence: 99%
“…While there are unanswered questions concerning the Trp-cage folding pathway, with a number of groups having reported data suggesting that Trp-cage folding is not a two-state system, 19,28,3335 these data are largely associated with structure melting analysis rather dynamics measurements. Both T-jump and NMR relaxation experiments are consistent with a net two-state process, with fewer exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, other computational studies on Trp-cage reported the partial formations of the helical elements in the unfolded state [1517, 20, 22, 23]. Similarly, experimental studies showed the existence of the helical elements in the unfolded state of Trp-cage [3, 11], and another experimental study emphasized the importance of preformed structure in the unfolded state for its fast folding [4]. The conformation at j = 300 shows the RMSD value of 5.6 Å, quite different from the native structure.…”
Section: Resultsmentioning
confidence: 92%
“…Due to the difficulties in the understanding of folding dynamics for large proteins, fragments of proteins (e.g., α -helix and β -hairpin) and small proteins have been mainly used to investigate protein folding dynamics. Recently, the 20-residue Trp-cage protein [1] with a fast folding rate [2] has attracted many researchers, both experimentalists [111] and theoreticians [1224], in the protein-folding research community.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the tryptophan residues in the structure stabilization has already been demonstrated for a number of peptides [25][26][27] and proteins [28,29]. Examples include e.g.…”
Section: Discussionmentioning
confidence: 96%